2021
DOI: 10.1371/journal.pone.0259823
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional investigation of SARS-CoV-2 seroprevalence and associated risk factors in children and adolescents in the United States

Abstract: Background Pediatric SARS-CoV-2 data remain limited and seropositivity rates in children were reported as <1% early in the pandemic. Seroepidemiologic evaluation of SARS-CoV-2 in children in a major metropolitan region of the US was performed. Methods Children and adolescents ≤19 years were enrolled in a cross-sectional, observational study of SARS-CoV-2 seroprevalence from July-October 2020 in Northern Virginia, US. Demographic, health, and COVID-19 exposure information was collected, and blood analyzed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
4
20
0
1
Order By: Relevance
“…12,13 Recently, a cross sectional investigation of SARS in Virginia reported 8•5% seropositivity in a study of 1,038 children; seroprevalence was highest (13•7%) in children in the 0-5 year age group. 14 Our data are consistent with the observation that rates of seropositivity are higher in LMIC settings and underscore the widespread distribution of infection in very young children in these areas, with no risk factors identified other than occurrence in the midst of an epidemic wave.…”
Section: Commentsupporting
confidence: 89%
“…12,13 Recently, a cross sectional investigation of SARS in Virginia reported 8•5% seropositivity in a study of 1,038 children; seroprevalence was highest (13•7%) in children in the 0-5 year age group. 14 Our data are consistent with the observation that rates of seropositivity are higher in LMIC settings and underscore the widespread distribution of infection in very young children in these areas, with no risk factors identified other than occurrence in the midst of an epidemic wave.…”
Section: Commentsupporting
confidence: 89%
“… 12 14 ). Beyond the neonatal period, infants may be at heighted risk of SARS-CoV-2 transmission from infected caregivers due to the frequency and intensity of close contact care and feeding ( 15 , 16 ), and may have higher risks of severe infection relative to older children due to less developed immune responses ( 6 , 17 , 18 ). Outcomes of breastfed children exposed to SARS-CoV-2 infected mothers are of further interest, as milk is not a source of SARS-CoV-2 transmission but is a source of persistent SARS-CoV-2 specific antibodies ( 19 23 ) and likely other antiviral agents ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some research shows that young children are less susceptible to infection than adults 33-35 , other research shows that children may be as likely as adults to become infected with COVID-19 36 . In fact, a recent epidemiologic study 37 of a pediatric sample in Virginia reported a SARS-CoV-2 infection rate (8.5%) that was higher than a sample of adults (2.4%) from a similar region and period 38 . Further, children appear to play a role in community transmission through their social interactions and hygienic habits 33 , a finding that underscores the importance of risk-mitigation strategies among youth especially as the COVID-19 pandemic continues to evolve and become even more transmissible, as in the case of the most recent circulating variant (Omicron).…”
Section: Discussionmentioning
confidence: 91%